The effect of Filipino overseas migration on the non-migrant spouse's market participation and labor supply behavior - Emily Christi A. Cabegin (Institute for the Study of Labor (IZA), 2006)
This paper examines the effect of one partner's overseas migration on the other non-migrant partner's labor force participation and supply behavior. I compare the effect when the migrant partner is male and when she is female. The study uses merged 2003 data sets from the nationally representative Labor Force Survey, the Family Income and Expenditures Survey and the Survey of Overseas Filipinos. Employing alternative empirical specifications of the labor supply function, the study examines the income remittance and the conjugal home-time effects of overseas migration. Addressing the potential endogeneity of income and migration, estimates establish stronger conjugal home time effects of migration for married women and larger remittance income effects for married men.
Keywords: F22; J22; J61; D1; O15; 330; Philippines; international migration; remittances; labor supply; conjugal-time allocation